Higher Atmospheric CO2 Levels Favor C3 Plants Over C4 Plants in Utilizing Ammonium as a Nitrogen Source - Wang, Feng; Gao, Jingwen; Yong, Jean W. H.; Wang, Qiang; Ma, Junwei; He, Xinhua (Frontiers in Plant Science, 2020)
Photosynthesis of wheat and maize declined when grown with NH4+ as a nitrogen (N) source at ambient CO2 concentration compared to those grown with a mixture of NO3– and NH4+, or NO3– as the sole N source. Interestingly, these N nutritional physiological responses changed when the atmospheric CO2 concentration increases. We studied the photosynthetic responses of wheat and maize growing with various N forms at three levels of growth CO2 levels. Hydroponic experiments were carried out using a C3 plant (wheat, Triticum aestivum L. cv. Chuanmai 58) and a C4 plant (maize, Zea mays L. cv. Zhongdan 808) given three types of N nutrition: sole NO3– (NN), sole NH4+ (AN) and a mixture of both NO3– and NH4+ (Mix-N). The test plants were grown using custom-built chambers where a continuous and desired atmospheric CO2 (Ca) concentration could be maintained: 280 μmol mol–1 (representing the pre-Industrial Revolution CO2 concentration of the 18th century), 400 μmol mol–1 (present level) and 550 μmol mol–1 (representing the anticipated futuristic concentration in 2050). Under AN, the decrease in net photosynthetic rate (Pn) was attributed to a reduction in the maximum RuBP-regeneration rate, which then caused reductions in the maximum Rubisco-carboxylation rates for both species. Decreases in electron transport rate, reduction of electron flux to the photosynthetic carbon [Je(PCR)] and electron flux for photorespiratory carbon oxidation [Je(PCO)] were also observed under AN for both species. However, the intercellular (Ci) and chloroplast (Cc) CO2 concentration increased with increasing atmospheric CO2 in C3 wheat but not in C4 maize, leading to a higher Je(PCR)/ Je(PCO) ratio. Interestingly, the reduction of Pn under AN was relieved in wheat through higher CO2 levels, but that was not the case in maize. In conclusion, elevating atmospheric CO2 concentration increased Ci and Cc in wheat, but not in maize, with enhanced electron fluxes towards photosynthesis, rather than photorespiration, thereby relieving the inhibition of photosynthesis under AN. Our results contributed to a better understanding of NH4+ involvement in N nutrition of crops growing under different levels of CO2.